2008
DOI: 10.1016/j.bbr.2007.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alcohol exposure during development on play behavior and c-Fos expression in response to play behavior

Abstract: Developmental exposure to alcohol can produce characteristic physiological and cognitive deficits, often termed Fetal Alcohol Spectrum Disorder (FASD). More recently, social deficits have been shown to occur both in FASD and animal models of FASD; the behavioral and neural bases of these deficits remain to be determined. It was hypothesized that changes in sensory processing may in part underlie the social deficits seen in FASD. This study used a rat model of FASD and social play, a behavior critical to adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 74 publications
(92 reference statements)
3
40
0
Order By: Relevance
“…Brunssen et al, 2013, Ey et al, 2011) in which sensory processing and social motivations have been impaired. The neural circuitry associated with altered social behavior in prenatal alcohol-exposed rodents is thought to include the somatosensory cortex, frontal cortex, amygdala, and nucleus accumbens (Lawrence et al, 2008, Hamilton et al, 2010a, Hamilton et al, 2010b). Although specific volume defects were not observed following GD8 alcohol exposure, shape defects of the corpus callosum suggest some abnormal wiring may have occurred that would impact function.…”
Section: Discussionmentioning
confidence: 99%
“…Brunssen et al, 2013, Ey et al, 2011) in which sensory processing and social motivations have been impaired. The neural circuitry associated with altered social behavior in prenatal alcohol-exposed rodents is thought to include the somatosensory cortex, frontal cortex, amygdala, and nucleus accumbens (Lawrence et al, 2008, Hamilton et al, 2010a, Hamilton et al, 2010b). Although specific volume defects were not observed following GD8 alcohol exposure, shape defects of the corpus callosum suggest some abnormal wiring may have occurred that would impact function.…”
Section: Discussionmentioning
confidence: 99%
“…3). The majority of rodent studies show that aggressive play is decreased in adolescent and adult males across PAE exposures (Charles Lawrence, Cale Bonner, Newson, & Kelly, 2008; Kelly & Dillingham, 1994; Lugo, Marino, Cronise, & Kelly, 2003; Meyer & Riley, 1986; Wellmann et al, 2015). However, some studies have shown increases in wrestling behaviors in males (Hamilton et al, 2010, 2014; Royalty, 1990).…”
Section: Effects On Social Behaviormentioning
confidence: 99%
“…Studies showing decreases in aggressive play behaviors utilized either high-dose gavage or moderate liquid-diet paradigms, which may result in short withdrawal periods and more stable BACs, respectively. However, in the two studies showing increased aggressive play behaviors, one utilized a 4-h voluntary drinking-in-the-dark paradigm and the other a lower dose gavage (2 g/kg/day compared to 3–5 g/kg/day) (Charles Lawrence et al, 2008; Royalty, 1990). In these paradigms, the withdrawal periods are most likely much longer.…”
Section: Effects On Social Behaviormentioning
confidence: 99%
“…In addition to altered social behavior, sensory detection and processing of somatosensory stimuli are also impaired following prenatal ethanol exposure [2, 6]. This may be due, in part, to the ethanol-induced alteration in the structure of somatosensory cortex [5, 26-30].…”
Section: Introductionmentioning
confidence: 99%